Government and business community attitudes towards cruise tourism development - Pivčević, Smiljana; Mandić, Ante; Šalja, Niko (Geographica Pannonica, 2018)
This study analyses government and business community attitudes towards cruise tourism impacts and its future development. An empirical study was conducted in Dubrovnik on a sample of 105 leaders in tourism-related organisations developing, validating and using the the Cruise Tourism Impacts scale. Research findings reveal a moderately positive attitude towards the cruise tourism impacts and the desired shift in future development priorities. Promotion, revenues and employment generation are the most pronounced positive impacts and cruise tourism influence on land-based guests the most pronounced negative one. Only sex and workplace are found to be discriminators of cruise tourism impacts perceptions. Implications for destination management and suggestions for future studies are provided.
Keywords: cruise tourism impacts; government and business stakeholders; discriminating variables; Dubrovnik